Potential impact of climate change on spatial distribution of two savannah amphibian species in West Africa - (:unkn) unknown (My University, 2023)
Abstract Climate change affects biodiversity, notably by modifying species habitats. In the West African savannahs, amphibian species are widespread. Despite their importance in ecosystems, little is known about the potential impacts of future climate change on these amphibians, hence the need to study the future distribution patterns of West African savannah amphibian species. We performed species distribution modelling to forecast the current and future distribution of two species Hyperolius nitidulus and Ptychadena bibroni in West Africa. Based on the global climate model MIROC5 and two future climate scenarios (RCP 4.5 and RCP 8.5), we assessed trends in the evolution of suitable habitat areas of these two amphibian species. We found that H. nitidulus is likely to lose significant proportions of their current habitats in the future due to climate change, while P. bibroni is likely to gain new suitable habitats. Our study suggests that some savannah amphibian species that are currently classified as Least Concern by the IUCN would be negatively affected by future climate change as shown by the distribution patterns of H. nitidulus . It is therefore necessary to consider all amphibian species, whether widely distributed or endemic, in future conservation strategies for amphibians in West Africa.
Keywords: African Research